Identification of Generalized Models of Development of Economic Systems of Rental Character Based on the Retrospective Analysis of World Experience - Matraeva, Liliia V.; Korolkova, Nataliya A. (International Journal of Energy Economics and Policy, 2019)
The rental nature of the economic system determines the availability of additional opportunities as well as the problems of its development. The decisive factor is the choice of a development model based on the system of state regulation of rental relations, including the search for effective combinations of state policy mechanisms. The core in most cases is energy policy and energy management as a development factor. Now we can talk about the accumulation of sufficient experience to conduct a comprehensive study of the peculiarities of the development of rental economies. The article reveals the experience of 24 countries of the world (30 cases) with a focus on the peculiarities of the formation and implementation of the state policy. The cluster analysis allowed us to identify three generalized models for the development of rental-type economic systems with a pronounced profile. This provides a basis for the identification of the main priorities. Keywords: rental-type economic system, state policy mechanisms, clustering. JEL Classifications: P510, O570, O110 DOI: https://doi.org/10.32479/ijeep.8178